EFEKTIVITAS TARIF HIBRIDA DALAM MENJANGKAU SEGMEN TAMU BERBASIS AFILIASI PEMESANAN KAMAR - Sukardi, Sukardi; Wibowo, Andri (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyse the effectiveness of implementing a hybrid rate strategy in reaching various guest segments based on room booking affiliation in the hotel industry in Indonesia. Hybrid rates combine static and dynamic rate elements that allow hotels to adjust prices according to the characteristics of booking channels and customer needs. A qualitative approach was used in this study through a guided survey of key informants consisting of hotel managers and leaders in various regions. The study's results indicate that hybrid rates are most effectively applied to the OTA, travel agent, and individual customer segments that are responsive to price changes. Meanwhile, the corporate and government segments still require a more stable rate structure, although it can be adjusted through contract negotiations and seasonal offers. The main obstacles in implementing this strategy include the limitations of the hotel's technology system, differences in customer perceptions of price, and difficulties in communicating rate policies transparently. This study concludes that the success of hybrid rates is largely determined by the hotel's ability to map the characteristics of booking affiliations, manage the price distribution system consistently, and build effective communication with customers